Meta-Analysis: The Effect of Breast Milk on Child Language - Abida, Liza Laela; Murti, Bhisma; Prasetya, Hanung (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: Language development is an individual's ability to master vocabulary, speech, grammar, and pronunciation ethics within a certain period of time according to age development. Breast milk is the best food for babies, because it contains all the nutrients needed in the right amount to promote a child's growth and development. The purpose of this study was to analyze the effect of breastfeeding on children's language development by using meta-analysis.Subjects and Method: This was a systematic review and meta-analysis. The articles used in this study were obtained from several databases including PubMed, Google Scholar, and Springer Link. The articles used in this study were those published from 1999-2020. The article search was carried out by considering the eligibility criteria defined using the PICO model. The population in the study were child